STRATEGI PEMBAHARUAN PENDIDIKAN DI SEKOLAH DAN MADRASAH : STRATEGI FASILITATIF, PENDIDIKAN, BUJUKAN, DAN PAKSAAN MOTIVASI MAHASISWA - Hajrawati, Hajrawati; Muspawi, Mohamad; Rahman, K.A.; Ali, Rd. M. (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
Educational reform in keeping up with the times through strengthening the strategic role of formal institutions such as schools and madrasahs. The facilitative strategy focuses on providing access, support, and opportunities that allow educators, students, and all stakeholders to develop their potential optimally. The research was conducted using a literature study approach that examines educational reform strategies, namely facilitative, educational, persuasion and coercion strategies. The four strategies are designed to optimize the process of educational change in accordance with existing social and institutional characteristics. The facilitative strategy focuses on providing facilities and training for educators, the educational strategy focuses on changing attitudes through information, the persuasion strategy uses a communication approach that builds awareness, while the coercion strategy relies on normative policies that are binding. This article concludes that the success of educational reform is largely determined by the suitability of the strategy to the social context and the readiness of all stakeholders to accept change.